Disaggregate Energy Consumption and Economic Growth in Pakistan: A Sectoral Analysis - Munir, Kashif; Nadeem, Sana (International Journal of Energy Economics and Policy, 2022)
This study analyzes the relationship between disaggregate energy consumption i.e. oil, coal, gas, and electricity consumption in different sectors with economic growth. The study uses annual time series data of Pakistan from 1972 to 2016 and applies ARDL bound test for cointegration, while Granger causality test is used for short run causality. Results showed that oil consumption in industrial and transport sector, gas consumption in fertilizer and power sector, and electricity consumption in industrial sector have positive and significant impact on economic growth in the long run. However, oil consumption in agricultural and power sector, coal consumption in power and brick kilns sector, gas consumption in cement sector, and electricity consumption in agricultural sector have negative and significant impact on economic growth. However, no causality exists between oil consumption and economic growth, while unidirectional causality exists from economic growth to coal consumption in brick kilns sector, gas consumption in industrial sector, and electricity consumption in agricultural sector in the short run. For sustainable energy supply, reduce the consumption of oil and coal to indigenously available resources, however, for sustainable economic growth, encourage industrial sector to use electricity, while fertilizer and power sector to use gas.